Cover Image. Issue 6 (June 2018) - Stowell, Rianne D.; Wong, Elissa L.; Batchelor, Hanna N.; Mendes, Monique S.; Lamantia, Cassandra E.; Whitelaw, Brendan S.; Majewska, Ania K.
Abstract : Cover: The cover, by Rianne D. Stowell et al., is based on the Research Article Cerebellar microglia are dynamically unique and survey Purkinje neurons in vivo, DOI:10.1002/dneu.22572 . Acrylic painting by Rianne D. Stowell.